Study of the decay Τ- → 2π-π+3π0VΤ - Anderson, S; Kubota, Y; Lee, S; O'Neill, J; Patton, S; Poling, R; Riehle, T; Savinov, V; Smith, A; Alam, MS; Athar, S; Ling, Z; et al. (1997)
The decay Τ- → 2π-π+3π0vΤ has been studied with the CLEO II detector at the Cornell Electron Storage Ring. The branching fraction is measured to be (2.85 ± 0.56 ± 0.51) × 10-4. The result is in good agreement with the isospin expectation but somewhat below the conserved-vector-current prediction. We have searched for resonance substructure in the decay. Within the statistical precision, the decay is saturated by the channels Τ- → π-2π0ωvΤ, 2π-π+ηvΤ, and π-2π0ηvΤ. This is the first observation of this ω decay mode and the branching fraction is measured to be (1.89-0.67+0.74 ± 0.40) × 10-4.